Cre-loxP-mediated genetic lineage tracing: Unraveling cell fate and origin in the developing heart - Wang, Tao; Chen, Xinzhe; Wang, Kai; Ju, Jie; Yu, Xue; Wang, Shaocong; Liu, Cuiyun; Wang, Kun (Frontiers in Cardiovascular Medicine, 2023)
The Cre-loxP-mediated genetic lineage tracing system is an essential means to construct the fate mapping of single-cell progeny or cell populations. Understanding the structural hierarchy of cardiac progenitor cells is conducive to unveil the mechanism of cardiac development and cell fate transformation. Several prospective Cre-loxP-based lineage tracing systems have been used to precisely analyze the fate determination and developmental characteristics of endocardial cells (ECs), epicardial cells, and cardiomyocyts. Therefore, emering lineage-tracing techniques advance the study of cardiovascular-related cellular plasticity. In this review, we illustrate the principles and methods of the emerging Cre-loxP-based genetic lineage tracing technology for trajectory monitoring of distinct cell lineages in the heart. The comprehensive demonstration of the differentiation process of single-cell progeny by means of genetic lineage tracing technology has made outstanding contributions to cardiac development and homeostasis, providing new therapeutic strategies for tissue regeneration in congenital and cardiovascular diseases (CVDs).